2021
DOI: 10.1016/j.xcrm.2021.100297
|View full text |Cite
|
Sign up to set email alerts
|

CAR T cells targeting tumor-associated exons of glypican 2 regress neuroblastoma in mice

Abstract: Targeting solid tumors must overcome several major obstacles, in particular, the identification of elusive tumor-specific antigens. Here, we devise a strategy to help identify tumor-specific epitopes. Glypican 2 (GPC2) is overexpressed in neuroblastoma. Using RNA sequencing (RNA-seq) analysis, we show that exon 3 and exons 7-10 of GPC2 are expressed in cancer but are minimally expressed in normal tissues. Accordingly, we discover a monoclonal antibody (CT3) that binds exons 3 and 10 and visualize the complex s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…CAR T cells that contain the variable fragment (Fv) of mAb 15B6 were produced using the vector developed by the M.H. laboratory ( 23 ). In this construct an Fv in which the light chain precedes the heavy chain is fused to a CD8 hinge ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR T cells that contain the variable fragment (Fv) of mAb 15B6 were produced using the vector developed by the M.H. laboratory ( 23 ). In this construct an Fv in which the light chain precedes the heavy chain is fused to a CD8 hinge ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Assays were performed as previously described ( 23 ). The binding kinetics were performed using the Octet RED96 system (FortéBio) at the Biophysics core at National Heart, Lung, and Blood Institute.…”
Section: Methodsmentioning
confidence: 99%
“…One promising strategy to overcome the paucity of true neoantigens is to target oncofetal antigens, a class of cell surface markers normally expressed exclusively during prenatal tissue development that can become re-expressed during neoplastic transformation (20). For example, CAR T-cells have been developed to target tumor-specific exons of the oncofetal antigen cerebroglycan GPC2 (21,22). Alternatively, they can be made to target tumor-specific antigen epitopes.…”
Section: Challenges Antigen Selectionmentioning
confidence: 99%
“…A research identified immunotherapy targets in 12 pediatric cancers, and GPC2 was analyzed in 8 diseases such as osteosarcoma (OS) and Ewing sarcoma (EWS), which makes it evident that GPC2 has a wide range of functions in childhood cancers ( 20 ). Some papers consider that it keeps silent relatively in various adult normal tissues such as brain, heart, lung, and kidney ( 9 , 21 ). However, small-cell lung cancer and prostate cancer were discovered to have an upregulated expression ( 17 , 22 ).…”
Section: Introductionmentioning
confidence: 99%